Understanding high school students' perception of nature and time spent outdoors across demographics. Issue 2 (3rd April 2019) - Bonnell, Kory J.; Hargiss, Christina L.M.; Norland, Jack E.
ABSTRACT: The purpose of this study was to assess high school students' perceptions of nature and the amount of time they spend outdoors. More than 200 tenth graders from different demographic locations in Minnesota, USA were surveyed to understand their perceptions of nature, their attitude towards it, as well as to gauge what activities students were participating in when outdoors. Results indicate that regardless of demographics, students seem to define and perceive nature similarly. Further, the study also found that time spent on a computer or in front of the television has decreased but greater time is spent on personal electronic devices.